The Weak Probability of Punishment for Environmental Offenses and Deterrence of Environmental Offenders: A Discussion Based on USEPA Criminal Cases, 1983–2013. Issue 10 (2nd October 2016) - Lynch, Michael J.; Barrett, Kimberly L.; Stretesky, Paul B.; Long, Michael A.
ABSTRACT: Numerous studies observe a decrease in environmental crimes following imposition of fines or penalties potentially due to general and specific deterrent effects. Here we explore whether those deterrent effects appear plausible by estimating the probability of a USEPA criminal case occurring each year between 1983 through 2013. Our analysis shows that there is an extremely low probability of an environmental crime case being prosecuted criminally by USEPA, casting doubt that these criminal cases are sufficiently widespread to generate a deterrent effect. We suggested that alternative theoretical orientations and policy initiatives be employed in studying and responding to environmental infractions.